A pure organic heterostructure of μ-oxo dimeric iron(iii) porphyrin and graphitic-C3N4 for solar H2 roduction from water. Issue 1 (1st December 2015) - Wang, D. H.; Pan, J. N.; Li, H. H.; Liu, J. J.; Wang, Y. B.; Kang, L. T.; Yao, J. N.
Abstract : A novel pure organic heterostructure was constructed between g-C3 N4 and (FeTPP)2 O as a photocatalyst for solar H2 production from water splitting. Abstract : Due to the two-dimensional flexible structure and abundant pendant amine, graphitic-C3 N4 (g-C3 N4 ) may be easily modified by organic molecules as a promising photocatalyst for solar H2 production from water. Here, through a simple liquid chemical reaction between g-C3 N4 and the precursor of μ-oxo dimeric iron(iii ) porphyrin [(FeTPP)2 O], we provide a novel route to construct a pure organic heterostructure of g-C3 N4 /(FeTPP)2 O on the basis of the π–π and the Fe–amine interactions. The experimental results demonstrated that (FeTPP)2 O acted not just as a photosensitizer, but also played the role of a charge promotor to prohibit the recombination of the excited electrons and holes of g-C3 N4 . As compared to pure or mixed g-C3 N4 and/or (FeTPP)2 O, the obtained pure organic g-C3 N4 /(FeTPP)2 O heterostructure exhibited dramatic photocatalytic H2 production under solar light without any cocatalysts.